THE ROLE OF ATTRACTIONS, SERVICE QUALITY AND FACILITIES IN SATISFACTION AND REVISIT INTENTION - Endang Sulistya Rini (Universitas Riau Kepulauan, 2023)
Many tourist destinations in Indonesia have great potential to develop and are widely known by tourists, both local and foreign tourists. One of the tourist areas in Indonesia is Lake Lau Kawar. There are still many tourism potentials of Lake Lau Kawar that have not been developed as tourism products for the welfare and improvement of the quality of life of the surrounding community, both in the form of natural beauty, natural phenomena and landscapes, as well as the way of life of the people. Facilities and infrastructure such as road facilities, transportation, lodging, restaurants, promotions, the application of sapta charms and other supporting facilities are inadequate. Communities around the tourist area also have not played a direct role in the development of the Lau Kawar Lake tourism object. This is thought to be the cause of tourists who have visited there not interested in visiting again. This study aims to determine and analyze the effect of Attractions, Service Quality, and Facilities on Revisit Intention through Satisfaction as a variable Intervening. The population in this study were cafe owners in the city of Kabanjahe, totaling 30 cafes. The number of samples in this study were 100 visitors to the Lake Lau Kawar tour using the accidental sampling technique. The data analysis method used is SEM-PLS. The results showed that Attractions had a positive and insignificant effect on Revisit Intention, Attractions had a positive and significant effect on Satisfaction, Service Quality had a positive and significant effect on Revisit Intention, Service Quality had a positive and significant effect on Satisfaction, Facilities had a positive and insignificant effect on Revisit Intention , Attraction has a positive and not significant effect on Satisfaction, Satisfaction has a positive and significant effect on Revisit Intention.